2019
DOI: 10.1080/03069885.2019.1633459
|View full text |Cite
|
Sign up to set email alerts
|

Arts for the blues – a new creative psychological therapy for depression

Abstract: Routinely prescribed psychological therapies for depression are not always effective. Arts therapies, particularly Dance Movement Psychotherapy, may offer additional therapeutic mechanisms for depression. Therefore, client-reported helpful factors from various therapy types, along with client preferences, are key in devising new therapeutic interventions. We present a framework for a new pluralistic 'meta-approach' of therapy for depression, based on an interdisciplinary thematic synthesis (Thomas & Harden, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…In-depth study of the manuals of the different types of DMT practice used can result in further refinement of what we think is currently responsible for the significant effects of DMT on reducing depression. A new project called “Arts for the Blues” (Haslam et al, 2019; Karkou et al, 2019; Parsons et al, in press) may offer relevant support in this direction for DMT as well as the other arts therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth study of the manuals of the different types of DMT practice used can result in further refinement of what we think is currently responsible for the significant effects of DMT on reducing depression. A new project called “Arts for the Blues” (Haslam et al, 2019; Karkou et al, 2019; Parsons et al, in press) may offer relevant support in this direction for DMT as well as the other arts therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, two systematic reviews were carried out to synthesize the evidence from arts therapies interventions delivered in primary mainstream schools (Moula, 2020;Moula et al, 2020). The findings showed that for a pilot study, a minimum of 60 participants (30 in each group for a twoarm intervention) may be statistically meaningful (Uttley et al, 2015), which is also confirmed in relevant methodological texts (Browne, 1995;Murphy et al, 2014). In a recent systematic review examining the clinical effectiveness of art therapy in those with non-psychotic mental health disorders (Uttley et al, 2015) the mean sample size was also found to be 52 participants.…”
Section: Methodsmentioning
confidence: 73%
“…During the workshop, this personal narrative took the form of a creative piece in the form of words, images or movement that was 'shared with others'. These ingredients were only a small selection of the full list of therapeutic ingredients presented and discussed in Parsons et al (24) although they held the essence of the proposed intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The workshop required contracting for safety, data protection and participants' rights, time to outline the project and explain the rationale as described in detail in Parsons et al, (24). As indicated in Table 1, the intervention part of the workshop began with the consideration of a small change a participant would like to make;…”
Section: What Was Included In the Workhopmentioning
confidence: 99%